Internalised stigma in mental health: An investigation of the role of attachment style. (December 2018) - Bradstreet, Simon; Dodd, Alyson; Jones, Steven
Highlights: Perceived public stigma was positively associated with internalised stigma. Anxious, but not avoidant, attachment was positively associated with internal stigma. Insecure attachment did not moderate the internalisation of stigma. There is though sufficient evidence to warrant further research. Abstract: Internalised stigma is associated with a range of negative outcomes, yet little is known about what determines the internalisation of stigma. In this study we examined the potential role of adult attachment style in the internalisation process in a transdiagnostic sample of adults with experience of recent mental health service use ( n = 122), using an online survey. Associations between internalised stigma and perceived public stigma were tested. We also examined whether anxious and avoidant (insecure) attachment styles were positively associated with a significant amount of variance in internalised stigma when controlling for other variables, and whether the relationship between perceived public stigma and internalised stigma was moderated by anxious and avoidant attachment. We found that internalised stigma, perceived public stigma and insecure attachment were commonly reported and that internalised stigma was positively associated with perceived public stigma. However, neither anxious or avoidant attachment were associated with a significant amount of variance in internalised stigma and we found no moderating effect on the relationship between perceived public stigma and internalised stigma for insecure attachment. Despite mixed results, the strength of association between anxious attachment and internalised stigma suggests further research, which addresses some limitations of the current study, is warranted.